2021
DOI: 10.1302/2633-1462.28.bjo-2021-0092.r1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and complications following revision shoulder arthroplasty

Abstract: Aims It is important to understand the rate of complications associated with the increasing burden of revision shoulder arthroplasty. Currently, this has not been well quantified. This review aims to address that deficiency with a focus on complication and reoperation rates, shoulder outcome scores, and comparison of anatomical and reverse prostheses when used in revision surgery. Methods A Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) systematic review was performed to identify c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 130 publications
0
19
0
1
Order By: Relevance
“…A previous review demonstrated superior shoulder scores following TSA revised to a RSA, compared to TSA revised to a TSA. 41 However it is unclear how the data synthesis was performed and broad inclusion criteria were used. No work could be found comparing implant choices when revising a hemiarthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…A previous review demonstrated superior shoulder scores following TSA revised to a RSA, compared to TSA revised to a TSA. 41 However it is unclear how the data synthesis was performed and broad inclusion criteria were used. No work could be found comparing implant choices when revising a hemiarthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic TSA has increased in usage from 9.5 cases per 100,000 persons in 2012 to 12.5 cases per 100,000 in 2017, and reverse TSA has increased in usage from 7.3 cases per 100,000 persons in 2012 to 19.3 cases per 100,000 in 2017 [ 4 ]. However, the postoperative complication rate for revision shoulder arthroplasty has been shown to be high at 22% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loosening of the glenoid component is the most common reason for revision after total shoulder arthroplasty (TSA) and may be responsible for 30% of revision procedures. 1 3 While TSA continues to be a frequently performed and effective treatment option for pain relief and improvement of function for degenerative shoulder conditions there remains concerns regarding implant longevity. 4 7 A recent population-based cohort study has estimated the lifetime revision rate for a failed primary TSA to be as high as 25%.…”
Section: Introductionmentioning
confidence: 99%
“… 11 However there is currently no consensus on the optimal surgical technique, as all of these proposed methods have been shown to have varying complication and reoperation rates. 1 , 12 15 Arthroscopic removal of the glenoid component (ARGC) after TSA has been proposed as an option for presumed aseptic polyethylene loosening ( Figures 1 and 2 ). 16 Proposed advantages of this technique include a less-invasive arthroscopic approach, which may be beneficial in older patients with multiple medical comorbidities due to the potential to avoid some complications associated with open revision.…”
Section: Introductionmentioning
confidence: 99%